Examining the L2 reading comprehension ability of adult ELLs: Developing a diagnostic test within the cognitive diagnostic assessment framework. (January 2021) - Toprak, Tugba Elif; Cakir, Abdulvahit
Cognitive diagnostic assessment (CDA) has been applied to language assessment in a number of studies in which a diagnostic classification model (DCM) was retrofitted to the results of a non-diagnostic assessment. However, the need to apply CDA through utilization of an inductive rather than a retrofitted approach has been a recurrent theme in these studies. Thus, this study aimed to develop a diagnostic L2 reading comprehension test in English to investigate adult examinees' reading performances in an EFL (English as a Foreign Language) academic setting. The test was based on a cognitive model of L2 reading comprehension and was administered to a sample of 1058 examinees across Turkey. The results were analyzed using log-linear cognitive diagnosis modeling (LCDM), which is one of the general DCM families subsuming other core DCMs. The findings of the study indicated that obtaining fine-grained diagnostic information about examinees' performances in a given domain would be possible by coupling an adequate understanding of the construct with a CDA framework.